Decoding the network of Trypanosoma brucei proteins that determines sensitivity to apolipoprotein-L1 - Currier, Rachel B.; Cooper, Anneli; Burrell-Saward, Hollie (PLoS pathogens, 2018)
In contrast to Trypanosoma brucei gambiense and T. b. rhodesiense (the causative agents of human African trypanosomiasis), T. b. brucei is lysed by apolipoprotein-L1 (apoL1)-containing human serum trypanolytic factors (TLF), rendering it non-infectious to humans. While the mechanisms of TLF1 uptake, apoL1 membrane integration, and T. b. gambiense and T. b. rhodesiense apoL1-resistance have been extensively characterised, our understanding of the range of factors that drive apoL1 action in T. b. brucei is limited. Selecting our bloodstream-form T. b. brucei RNAi library with recombinant apoL1 identified an array of factors that supports the trypanocidal action of apoL1, including six putative ubiquitin modifiers and several proteins putatively involved in membrane trafficking; we also identified the known apoL1 sensitivity determinants, TbKIFC1 and the V-ATPase. Most prominent amongst the novel apoL1 sensitivity determinants was a putative ubiquitin ligase. Intriguingly, while loss of this ubiquitin ligase reduces parasite sensitivity to apoL1, its loss enhances parasite sensitivity to TLF1-dominated normal human serum, indicating that free and TLF1-bound apoL1 have contrasting modes-of-action. Indeed, loss of the known human serum sensitivity determinants, p67 (lysosomal associated membrane protein) and the cathepsin-L regulator, ‘inhibitor of cysteine peptidase’, had no effect on sensitivity to free apoL1. Our findings highlight a complex network of proteins that influences apoL1 action, with implications for our understanding of the anti-trypanosomal action of human serum.
Gesehen am 01.04.2019